The Extent of Applying Corporate Governance Requirements According to International Specification (ISO 26000:2010) in the National Insurance Company: A Research Application (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract                The research aims to identify the application of corporate governance requirements according to the international standard (ISO 26000:2010) in the National Insurance Company. Strengths and weaknesses were identified to study the current state of this requirement's application in the company under investigation. The descriptive-analytical approach was utilized through a checklist derived from ISO 26000:2010. Several personal interviews and field visits were conducted to understand the extent of application and documentation based on various statistical methods. The results revealed a level of application in the corporate governance requirement of 59%, with a gap size of 41%, indicating non-conformity with the international specification. The findings call for the company's attention to corporate governance requirements.